MEDIA PEMBELAJARAN KAMUS TIGA BAHASA NEGARA BERBASIS ANDROID - Nora Yuris Prudensi; Masrizal Masrizal; Mustafha Haris Munandar (Politeknik Bisnis Indonesia, 2021)
The purpose of this study is to create a dictionary application in three languages that can help users to make it easier to search for English, Korean and Indonesian vocabulary. Dictionary of 3 State Languages is a learning media that can provide convenience for students and the general public. The phenomenon that occurs is that students in the class have problems with foreign languages to complete the tasks given by the teacher in fulfilling the learning contributions needed in the learning process in foreign language subjects. This application is designed using UML, Eclipse and SQLite database. The design of this application is very useful for students, teachers, and even the general public. The method used in designing this application is the Waterfall System Development Life Cycle method. The stages carried out consist of data collection, analysis of problems and requirements, and testing. Data collected from Indonesian dictionaries, Japanese dictionaries, English dictionaries and preparatory software is required to build an application. The next step is to build an application with Eclipse and the last process is to complete the application and implement it to an android device which provides vocabulary translation services into three languages at once.